IMPLEMENTASI DAN SOSIALISASI MODEL PELATIHAN DALAM PEMBERDAYAAN PENDUDUK MISKIN PERKOTAAN - Banowati, Eva; Paramita, Aulia Pradnya (Universitas Negeri Semarang, 2015)
Purpose of the study: 1) To improve the poor citizen’s skill of processing waste into compost, 2) To describethe steps of implementation and socialization of training model based on effectively empowerment to impovepoor citizen’s skill. Action research used in Semarang, socialization used in Pati. Study of population is poorBLSM receiver, sampling was used snowball method. The primary data of observation was taken duringtraining. Descriptive analysis techniques and used of cross table. Sub-model of training On The Job Trainingwith deductive and inductive methods can improve processing skills by 38%. Sustainability empowerment isused on training of sub-model of Off The Job Training- socialization method was used to build the integrityof the knowledge, attitudes, and skills of the poor trainee in improving the quantity and quality of theproduct. The effectiveness of the success of training model is ranging between 53, 75% to 71.75%. Thefindings in this study are implications of theoretical and managerial implications can provide a practicalcontribution to the deductive training management and inductive apprenticeship.